Supplier Sustainable Integrity Using a Split-half Method: Empirical Evidence from Malaysia - Fernando, Yudi; Gui, Anderes; Sari Wahyuni-TD, Ika; Won Seo, Yong; Haron, Hasnah (KnE Social Sciences, 2019)
The objective of this study is twofold accordingly. First, it aims to explore the measurement items of sustainable supplier integrity drivers. Second, it purports to investigate the relationship between drivers and supplier sustainable integrity. Furthermore, this study collected data from manufacturing firms in Malaysia. The targeted respondents were procurement managers and other decision-makers in the manufacturing companies. This study examined using a split-half method. First half data set was examined using exploratory factor analysis (EFA). The supplier assessment, supplier collaboration, and supplier codes of conduct were identified as drivers of sustainable supplier integrity. The other half of the data set used to develop a theoretical model. It was then established to test the model assessment and hypothesis testing. Thus, this study may shed light on finding answers on the importance of supplier codes of conduct. This is as the strongest driver in the theoretical model of the study. The possible reason behind this is because the manufacturing firms should inform supply chain network on essential of supplier codes of conduct to avoid corporate fraud and leverage business sustainability.